CTIM-22. THE COMBINATION OF LOMUSTINE AND THE IMMUNOCYTOKINE L19TNF IS A PROMISING TREATMENT FOR RECURRENT GLIOBLASTOMA. (14th November 2022) - Look, Thomas; Puca, Emanuele; Stucchi, Riccardo; De Luca, Roberto; Roth, Patrick; Neri, Dario; Weller, Michael; Hemmerle, Teresa; Weiss, Tobias
Abstract: Glioblastoma is the most aggressive primary brain tumor and adults and poorly immunogenic. Treatment options for recurrent glioblastoma after standard of care chemoradiation are limited Several immunotherapeutic strategies including peptide vaccination and immune checkpoint inhibition have so far failed to improve survival and except from potentially regorafenib, no other agent has demonstrated superior activity to lomustine. Therefore, there is an urgent need for more effective treatment strategies for recurrent glioblastoma. Here, we investigate a new treatment combination based on the alkylating chemotherapy lomustine and the tumor-stroma targeting antibody-cytokine fusion protein L19TNF in preclinical glioma models and patients with recurrent glioblastoma. The combination treatment with lomustine and L19TNF demonstrated strong synergistic anti-tumor activity in several immunocompetent orthotopic glioma models curing the majority of tumor-bearing mice, whereas other mono- or combination therapies for example with anti-PD1 had only limited anti-glioma activity. Investigations of the mechanism of action revealed that lomustine plus L19TNF led to intratumoral necrosis, DNA damage and triggered a strong local anti-tumor immune response with increased MHC-I expression, presentation of neoepitopes and increased abundance of tumor-infiltrating lymphoid cells. In the first patients treated within a phase I/II clinical trial (NCT04573192), the treatment was well tolerated, and durable objective tumor responses and disease stabilizations could be observed also in patients with an unmethylated MGMT promoter.